Association between body image satisfaction and depressive symptoms among young women in the UAE with Polycystic Ovary Syndrome (PCOS) and Non-PCOS: A comparative quantitative cross-sectional study - Shaima Abdrahman AlMekhlafi; Maria Susana Campo-Redondo (PLoS ONE, 2026)
Background Polycystic Ovary Syndrome (PCOS) is one of the most common conditions affecting women of reproductive age, significantly impacting both physical and psychological well-being, often leading to depressive symptoms and lower body image satisfaction. The prevalence of Polycystic Ovary Syndrome among women in the United Arab Emirates (UAE) is increasing. However, the psychological effects of Polycystic Ovary Syndrome on women in the UAE remain underexplored due to cultural sensitivities surrounding reproductive health. This cross-sectional study examines the association between depressive symptoms and body image satisfaction among young women in the UAE, comparing those with and without Polycystic Ovary Syndrome. The study surveyed 221 women aged 18–30, with 94 having Polycystic Ovary Syndrome and 127 without. Data were collected using the Patient Health Questionnaire-9 (PHQ-9), Body Image Concern Inventory (BICI), and Body Areas Satisfaction (BAS) subscales, and analyzed with Statistical Package for the Social Sciences (SPSS). Results Women with Polycystic Ovary Syndrome reported significantly higher levels of depressive symptoms and body image concerns, along with lower body satisfaction, compared to those without Polycystic Ovary Syndrome. While a higher Body Mass Index (BMI) correlated with lower body satisfaction, no significant association was found between Body Mass Index and depressive symptoms. Conclusion These findings highlight the psychological impact of Polycystic Ovary Syndrome on young women in the UAE, emphasizing the need for targeted mental health interventions and increased awareness.